Research Progress on the Relationship between Dietary Patterns and Hyperuricemia - Tian Long; Liang Liu (Applied Bionics and Biomechanics)
As the final metabolite of purine metabolism, uric acid is critically associated with human health. The serum uric acid level is regulated by diet and the metabolic capacity of the human body. The impaired control of uric acid metabolism and excretion is associated with the increased level of serum uric acid, which ultimately results in hyperuricemia. Hyperuricemia is the “fourth-highest” after hypertension, hyperglycemia, and hyperlipidemia. With progress made in the relationship between diet and hyperuricemia, different dietary patterns and lifestyles have been discussed, such as exercise, the amount intake of meat, seafood, supplements with omega-3 fatty acids, sugar-sweetened soft drinks and energy drinks, and lower-fat-containing foods as well as drinking beer, wine, and spirits in the present article. This study demonstrated that a lower risk of hyperuricemia is substantially correlated with higher baseline adherence to MeDiet, and plant polyphenols can combat hyperuricemia by blocking xanthine oxidase.